Hyers–Ulam Stability of Linear Homogeneous Quaternion-Valued Difference Equations - Wang, Jiangnan; Wang, JinRong; Liu, Rui (Qualitative theory of dynamical systems, 2023)
In this paper, we consider the Hyers–Ulam stability of the first-order linear homogeneous quaternion matrix difference equation. Furthermore, we prove the Hyers-Ulam stability of the second-order linear homogeneous quaternion-valued forward and backward difference equation by converting them into the first-order quaternion matrix difference equation. Finally, some examples are given to support the theoretical results.